Pentingnya pendidikan multikultural bagi masyarakat urban - Dahlan, Mubarak (Rayhan Intermedia, 2025)
The development of society and social changes resulting from advances in information technology today make multicultural education an urgent necessity, especially for urban communities living in an environment of diversity in terms of ethnicity, culture, religion, and language. The dynamics of urbanization, which give rise to increasingly complex social interactions, are highly susceptible to friction between groups if not accompanied by mutual understanding and respect among community members. This paper discusses the importance of multicultural education, particularly in shaping awareness, tolerance, and adaptability among urban communities. Through a literature review approach, this paper builds the perception that multicultural education actually functions not only as a means of introducing cultural differences in diversity, but also as a strategy to strengthen social cohesion, reduce discrimination, and create social harmony in urban public spaces. The results of the discussion show that, conceptually, multicultural education has a strategic role in building an inclusive, fair urban society that is capable of facing various challenges of globalization